Scientometric Review of Research Trends on Public Private Partnership (PPP) for Infrastructure Projects From 2000 to 2020 - Tam, Nguyen Van (CSID Journal of Infrastructure Development, 2021)
In the construction industry, public-private partnership (PPP) has been becoming increasingly common. While real-world PPP for infrastructure projects have been reported in many journals, published work on systematically summarizing what they have already provided remains limited. Based on the 1749 publications on PPP for infrastructure collected from the Scopus database for the period of 2000-2020, this study conducted a scientometric analysis in terms of annual publications, regional distribution, active contributors, published journals, co-occurrence keywords, and main research themes of previous studies. This paper found that there was a significant increase in the number of publications on PPP for infrastructure since 2008. Researchers from the USA, China, and Australia have been the main contributors to this research area. In addition, four main themes of research on PPP for infrastructure are explored, and several research gaps and research directions in this area are established for further studies.